Extrusion product made from sweet potato - Umar Santoso; Triastati Murdaningsih; Rob Mudjisihono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2007)
The objective of the research was to develop a method to prepare extruted product from sweet potato and rice flour with addition of karabenguk as the protein source. The ratio of sweet potato and rice flour were 90:10; 75:25; and 55:45, and the addition of korobenguk flour varied from 0.5;1.0to 1.5 % (on the mixture basis). The first step was to determine the optimum condition for extrusion process. The extruded product was evaluated for its chemical, physical, and sensory properties. The results showed that the extruded products can be produced from sweet potato and rice flour in all ratios experimented. The addition of korobenguk flour appeared to increase protein, fat, and ash contents but decrease the extension degree the extension degree, crispness, and water absorption index. Based on the sensory evaluation, the most preferred product was that prepared from 55% sweet potato flour, 45% rice flour, and addition of 0.5% korobenguk flour (on the basis of the dough) with moisture content of 15 %. Key words: sweet potato, extrusion product, korobenguk